2015
DOI: 10.1093/ntr/ntv109
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Metabolism in Young Adult Daily Menthol and Nonmenthol Smokers

Abstract: Introduction: Menthol cigarette smoking may increase the risk for tobacco smoke exposure and inhibit nicotine metabolism in the liver. Nicotine metabolism is primarily mediated by the enzyme CYP2A6 and the nicotine metabolite ratio (NMR = trans 3′ hydroxycotinine/cotinine) is a phenotypic proxy for CYP2A6 activity. No studies have examined differences in this biomarker among young adult daily menthol and nonmenthol smokers. This study compares biomarkers of tobacco smoke exposure among young adult daily mentho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…37 Salivary cotinine levels are a composite measure of nicotine and could be affected by the way the smoker absorbs or processes nicotine. Some research 38-40 suggests the theory that menthol could inhibit nicotine/cotinine metabolism, which could explain participants having higher salivary cotinine levels when smoking the nonmenthol test cigarette. African American smokers reportedly smoke fewer cigarettes per day than white smokers but have a higher incidence of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…37 Salivary cotinine levels are a composite measure of nicotine and could be affected by the way the smoker absorbs or processes nicotine. Some research 38-40 suggests the theory that menthol could inhibit nicotine/cotinine metabolism, which could explain participants having higher salivary cotinine levels when smoking the nonmenthol test cigarette. African American smokers reportedly smoke fewer cigarettes per day than white smokers but have a higher incidence of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Benowitz and colleagues (2004) demonstrated that smoking menthol cigarettes reduced nicotine clearance by ~11%. In a multiethnic sample of young adult daily smokers, the NMR was found to be significantly lower among menthol compared with nonmenthol smokers after adjusting for race/ethnicity, gender, BMI, and cigarettes smoked per day (0.19 vs. 0.24, p=.03; (Fagan et al 2015). Alcohol use is positively associated with NMR (Chenoweth et al 2014) but the mechanism underlying this association is yet to be determined.…”
Section: The Nicotine Metabolite Ratio As a Biomarker Of Nicotinementioning
confidence: 96%
“…Up-regulation of nAChRs has been observed in mice following chronic exposure to menthol concentrations comparable to those in cigarette smoke (Henderson et al, 2016) and in human menthol cigarette smokers (Brody et al, 2013). Menthol may also slow nicotine metabolism (Alsharari et al, 2015; Benowitz et al, 2004; Fagan et al, 2016). …”
Section: Introductionmentioning
confidence: 99%